Speciation of antimony in polyethylene terephthalate bottles - Martin, Ronald R.; Shotyk, William; Naftel, Steven J.; Ablett, James M.; Northrup, Paul (X-ray spectrometry, 2010)
Antimony contamination has been reported in drinking water from polyethylene terephthalate (PET) bottles. Micro-X-ray fluorescence (XRF) analysis has been used to identify the distribution and chemical form of residual antimony used as a catalyst in the manufacture of PET bottles. The results are consistent with clusters of Sb(III) having dimensions of the order of tens of micrometers, clearly showing the ability of synchrotron radiation analyses to both map elemental distribution and determine oxidation state. Copyright © 2010 John Wiley & Sons, Ltd.
Gesehen am 23.05.2023